2011
DOI: 10.1016/j.jmatprotec.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Dry machining of Inconel 718, workpiece surface integrity

Abstract: a b s t r a c tIn the machining of Inconel 718, nickel based heat resistant superalloy and classified difficult-to-cut material, the consumption of cooling lubricant is very important. To reduce the costs of production and to make the processes environmentally safe, the goal is to move toward dry cutting by eliminating cutting fluids. This goal can be achieved by using coated carbide tool and by increasing cutting speed.The present paper firstly reviews the main works on surface integrity and especially residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(173 citation statements)
references
References 19 publications
(30 reference statements)
7
121
0
10
Order By: Relevance
“…Zawartość twardych faz węglikowych w strukturze krystalicznej przyspiesza zużywanie się ostrza podczas obróbki. Niska przewodność cieplna utrudnia odprowadzanie ciepła ze strefy obróbki, a wysoka wytrzymałość na rozciąganie uniemożliwia stosowanie dużych głębokości skrawania [4,6,12]. Ze względu na swoje specyficzne właściwości obróbka stopu niklu Inconel 718 wymaga odpowiedniego doboru parametrów i warunków technologicznych oraz materiału narzędziowego.…”
Section: Wprowadzenieunclassified
“…Zawartość twardych faz węglikowych w strukturze krystalicznej przyspiesza zużywanie się ostrza podczas obróbki. Niska przewodność cieplna utrudnia odprowadzanie ciepła ze strefy obróbki, a wysoka wytrzymałość na rozciąganie uniemożliwia stosowanie dużych głębokości skrawania [4,6,12]. Ze względu na swoje specyficzne właściwości obróbka stopu niklu Inconel 718 wymaga odpowiedniego doboru parametrów i warunków technologicznych oraz materiału narzędziowego.…”
Section: Wprowadzenieunclassified
“…The result concluded that cutting force variation was probably due to temperature rise in the shear plane area. Devillez et al [7] analyzed the effect of cutting force component in dry turning of Inconel 718. The result revealed that cutting speed is the predominant factor to control the forces in turning operation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zbyt niska jej wartość powoduje silne drgania samowzbudne i nadmierne zużycie narzędzia, a zbyt duża wartość v c prowadzi do wzrostu temperatury w strefie skrawania oraz intensywnego zużycia powierzchni przyłożenia części roboczej narzędzia. Zaleca się stosowanie prędkości w zakresie 20 ÷ 90 m/min dla popularnych materiałów narzędziowych [2,3,9,11,15]. Głębokość skrawania a p zazwyczaj nie przekracza 1 mm, a posuw na ostrze f z zawiera się w przedziale 0,05 ÷ 0,2 mm [2,5,9,10,11,15].…”
Section: Badania Porównawcze Wybranych Wskaźników Skrawalności W Procunclassified